A national minimum wage; an inquiry - Great Britain (London: HMSO, 1969)
This report of an interdepartmental working party based on an inquiry on the British national minimum wage.
Bibliographical footnotes.
asm; 26/02/19
Loans
Keywords: Minimum wage; Great Britain